A Guide to Assessing the Political Economy of Domestic Climate Change Governance - Worker, Jesse; Palmer, Niki (World Resources Institute, 2021)
This paper discusses how understanding the domestic political economy of climate governance is critical for developing informed strategies to build and sustain political ambition. It provides guidance and a methodology for domestic stakeholders to determine the types of institutional reforms, incentives, coalitions, and policy design that can entrench long-term political support for climate ambition. The assessment can also help users identify political barriers to more equitable climate action and identify reforms that may strengthen inclusion and accountability. EXECUTIVE SUMMARY Highlights ▪ There is overwhelming evidence of the social, economic, and environmental case to reduce greenhouse gas (GHG) emissions and rapidly scale up adaptation. Yet, despite a proliferation of climate laws and policies over the last 10–15 years, emissions are still rising, and adaptation needs remain urgent. ▪ This calls for a more sophisticated assessment of the political economy factors that may enable or constrain implementation of policies and actions and sustain political commitment at the country level. ▪ This guide offers an assessment methodology to understand how structural factors, rules and norms, stakeholders and interests, and ideas and narratives influence the political economy of climate action in a given country context. ▪ The methodology was developed on the basis of climate policy, governance, and political economy literature with contributions from subject matter experts. ▪ We intend the assessment to support civil society coalitions, reform-minded civil servants and politicians, international organizations, and other stakeholders. ▪ The resulting analysis should deepen the understanding of context while informing the advocacy, policy design, coalition building, capacity building, and communications of domestic stakeholders.
Keywords: #Reviews & Framing / Revisões e Organização; L - english / inglês; M - methodology / metodologia; M - political economy analysis (PEA) / análise de economia política (AEP); governance / governação

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde